Serum Hepcidin Levels in Childhood-Onset Ischemic Stroke: A Case-Control Study. Issue 9 (March 2016) - Azab, Seham F.; Akeel, Nagwa E.; Abdalhady, Mohamed A.; Elhewala, Ahmed A.; Ali, Al Shymaa A.; Amin, Ezzat K.; Sarhan, Dina T.; Almalky, Mohamed A.A.; Elhindawy, Eman M.; Salam, Mohamed M.A.; Soliman, Attia A.; Abdellatif, Sawsan H.; et al.
Abstract : Abstract: Recently, hepcidin, an antimicrobial-like peptide hormone, has evolved as the master regulator of iron homeostasis. Despite the growing evidence of iron imbalance in childhood-onset ischemic stroke, serum hepcidin level in those patients has not yet been researched. In this study, we aimed to estimate serum (hepcidin) level in acute ischemic stroke (AIS) patients and to investigate whether subcutaneous enoxaparin sodium, which is a low-molecular-weight heparin (LMWH) derivative, could modulate serum hepcidin level in those patients. This was a case–control study included 60 (AIS) cases, and 100 healthy children with comparable age and gender as control group. For all subjects' serum hepcidin, interleukin-6 (IL-6), and soluble transferrin receptor [sTfR]) levels were assessed by (enzyme-linked immunosorbent assay [ELISA] method). Iron parameters including (serum iron, ferritin, transferrin, and total iron binding capacity [TIBC]) were also measured. The patients were subdivided according to treatment with an LMWH derivative into 2 groups and serum hepcidin levels were assessed initially and 1 week after stroke onset for all cases. We found that AIS cases had higher serum iron, ferritin, and IL6 levels compared to the control group (all P  < 0.01). Serum hepcidin was significantly higher in AIS cases (median, 36[15–73]ng/mL) compared to the control group (median, 24[10–41]ng/mL; P  < 0.01). On the 1st day of AIS diagnosis, serum hepcidin levels were similar in both stroke subgroups ( P  > 0.05). However, on the 7th day of diagnosis serum hepcidin level decreased significantly in AIS cases treated with LMWH (group 1) (median, 36 vs 21 ng/mL; P  < 0.01, respectively). Meanwhile, no significant change was observed in serum hepcidin level in AIS cases not treated with LMWH (group 2) ( P  > 0.05). Serum hepcidin showed significant positive correlations with serum iron, transferrin saturation, ferritin, and IL6 ( r  = 0.375, P  < 0.05; r  = 0.453, P  < 0.05; r  = 0.687, P  < 0.01; r  = 0.515, P  < 0.01; respectively). Our data brought a novel observation of elevated serum hepcidin level in pediatric AIS patients and pointed out that treatment with LMWH could modulate hepcidin level in those patients.